Health Hazard Posed by some Heavy Metals in Matte “Paint” Lipstick - Bello, Isaac Asusheyi; Umoren, Idorenyin Effiong; Ugboaja, Vincent Chijioke (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The levels of toxic and heavy metals in 15 matte lipsticks from 5 different brands (three colours (pink, purple and red) each) were assessed. The matte lipsticks samples were bought from Samaru market in Zaria, Kaduna State, Nigeria, after a poll had been conducted on female students of the Ahmadu Bello University main campus, Zaria, to discover commonly used lipstick types and colours. The lipsticks samples were analyzed for lead, cadmium, chromium, magnesium, zinc and iron. All the samples contained; lead, within the range, 85.20±0.02 ppm – 148.48±0.03 ppm, iron, 30.64±0.05 ppm – 488.16±0.04 ppm, zinc, 3.20±0.12 ppm – 90.80±0.16 ppm and magnesium, 134.88±0.04 – 991.44±0.04 ppm. The metals had average concentration of 120.9 ppm, 216.9 ppm, 25.73 ppm and 510.0 ppm for lead, iron, zinc, and magnesium respectively. Out of the analyzed sample, 6.67% contained chromium (1.36±0.14 ppm) with an average concentration of 0.091 ppm and 46.67% contained cadmium (0.08±0.01 ppm – 0.40±0.02 ppm) with an average concentration of 0.091 ppm. The results also showed that lead and cadmium in Beyond Beauty (purple), IMAN (purple, red and pink), Romantic (purple, red and pink), chromium in Beyond Beauty (purple), iron in all the samples except Romantic (purple), magnesium in Beyond Beauty (red and pink), Jully Rose (red), First Class (red and pink), IMAN (purple and pink) were higher than the permissible limit in food as determined by WHO. The safety of cosmetics, especially lipsticks, should be assessed regularly not only for the presence of hazardous contents, but also by comparing estimated exposures with health-based standards.